45 The anatomy of failure: can 100% repair rate of the degenerative mitral valve be achieved. (7th October 2015) - Kelly, R; Lyons, F; Granahan, A; Tolan, M
Abstract : Objectives: Despite Class 1 evidence that mitral repair is better than replacement, in the USA the repair rate is only just over 50% in degenerative mitral valve disease. A majority of surgeons do five or less mitral operations per year. We looked at our results over a ten year period and in particular we looked at the anatomy of our failed repairs and our re repairs to establish if using a different technique or strategy could bring the repair rate towards 100%. Methods: Valves were repaired using classical Carpentier repair techniques but also with wide use of PTFE neochordal implantation and pericardial patches. Much of the data was collected using the UK and Ireland Cardiac Surgical Dataset. Results: Between January 2005 and December 2014, 545 consecutive patients underwent surgery for degenerative mitral regurgitation. The overall inhospital mortality and rate of repair were respectively 1.1% and 95.2% for the whole cohort and 0.4% and 99.6% for elective non rheumatic (non calcified valve) operations. The rate of re operation for residual recurrent mitral regurgitation was 0.5% with a mean follow up of 40 months. 68% of patients were male, 15% in NYHA 1 and 38% in NYHA III/IV. 36% had evidence of atrial fibrillation preoperatively. 3.6% had echocardiographic evidence of moderate or severe MR at a mean follow up of 24 months postoperatively. Of the 20 patients with failed repairs, 12 had endocarditis and grossly destroyed valves. Seven had partially calcified leaflets leading to SAM after repair and had to be replaced. The one degenerative valve had a very unusual posterior leaflet in that it was very enlarged and wrapped around a non enlarged anterior leaflet. PTFE neochordal did not produce a competent repair, and resection of redundant tissue equally was not satisfactory, so the valve was replaced. Of the three patients attending for re repair two had dehiscence of the annuloplasty ring, three and four years after initial surgery and one had further chordal rupture. Conclusions: High volume units can produce very high rates of repair for mitral regurgitation. Endocarditis, and partially calcified leaflets still preclude some valves from being repaired. Very close to 100% repair rate can be achieved for other degenerative mitral regurgitation.